Diseño y construcción de una prensa de calor, para plásticos y materiales compuestos (2019)
The present work describes the design and construction of a device that applies pressure and temperature in a controlled manner, to mixtures of materials (polymers, plastic, plastic card-board, etc.), with the aim of producing modules and various forms, from recycled wood and polymers, to be used in different applications in the basic furniture industry. At each stage of the present work, an evaluation of functionality was carried out, supported by physical, load and stability tests, to verify the autonomy and operation of the obtained products. The develop-ment of this equipment is produced within the project “Manufacture of alternative elements from recyclable materials”, and as a result a device is obtained with which a process of handling, transformation and manufacture of new products based on recyclable materials is carried out, with the advantage that it eliminates the use of water in each stage and decreases the number of operations in the transformation process.